The Influence of the Cornell Note-Taking Method on Students’ Reading Comprehension of Explanation Text - Mutiara Qolby, Assyifa; Meisuri, Meisuri; Suci suryawati, Sri (Jompa Research and Development, 2025)
The Cornell note-taking method is a method of note-taking that helps students organize important information from a text systematically to support reading comprehension. The purpose of this study was to determine the influence of the Cornell note-taking method on students' reading comprehension skills before and after instruction using this Note-taking method. This study employed a quantitative with a quasi-experimental design. The research subjects consisted of 62 eleventh-grade students at SMA Negeri 12 Bandar Lampung, divided into an experimental class and a control class. Data were collected through pre-tests and post-tests and subsequently analyzed using statistical procedures. The results revealed a significant difference between the two groups. The experimental class, which applied the Cornell note-taking method, scored an average of 55.32 on the pre-test and increased to 76.61 on the post-test, showing an increase of 21.29 points. Meanwhile, the control class, which did not receive the same treatment, showed a modest improvement from 57.90 to 63.55, an increase of 5.65 points. based on the scores obtained, the Cornell note-taking method showed a positive influence on students' reading comprehension. Therefore, this method can be considered a useful method to support reading instruction, especially for explanation texts at the high school level.